The effect of phytase levels in the diet on the digestibility and growth performance of white shrimp Litopenaeus vannamei - Suprayudi, Muhammmad Agus; Harianto, Dini; Jusadi, Dedi (Indonesian Society of Scientific Aquaculture (ISSA), 2012)
This experiment was conducted to evaluate the effect of phytase levels in the diet on the digestibility and growth performance of white shrimp Litopenaeus vanname. White shrimp were used in the trial with initial body weight of 3.8±0.01 g were reared in aquarium (60×40×50 cm3) and filled with 60L treated sea water at a density of ten individu. Experimental diet were formulated in isonitrogeneous (36% protein) and isocaloric (3960 kcal/kg) to contain four levels of phytase: 0 iu/kg (diet A), 500 iu/kg (diet B), 750 iu/kg (diet C), and 1000 iu/kg(diet D). All diets were supplied with 0.5% of Cr2O3 as an indicator for digestibility measurement shrimp fed three times daily at satiation levelfor how many days of rearing. A factorial completely randomized experimental design was selected consisted of four treatments and triplicates. The result showed that the phytase addition improved the digestibility of protein, calcium, and phosphor as well as improve growth performance of white shrimp. Based on evaluation of those parameters, it is concluded that phytase level of500 IU support the best growth performance ofjuvenile white shrimp. Keywords: phytase, feed digestibility, growth,Litopenaeus vannamei